First insights into the genetics of 21-hydroxylase deficiency in the Roma population - Mirjana Kocova; Violeta Anastasovska; Aleksandar Petlichkovski; Henrik Falhammar (Wiley, 2021)
21-hydroxylase deficiency (21OHD) is an autosomal recessive disorder with an incidence of 1:10,000-1:20,000 and is the result of various mutations in the CYP21A2 gene. 21OHD has been described in many different populations, but it has not been studied in Roma individuals so far. The aim of the study was to analyse the genotype in Roma patients with 21OHD and the prevalence of the disease in the Roma population of North Macedonia.